Intermittent Negative Blood Cultures in Staphylococcus aureus Bacteremia; a Retrospective Study of 1071 Episodes. (18th November 2019) - Stewart, James D; Graham, Maryza; Kotsanas, Despina; Woolley, Ian; Korman, Tony M
Abstract: Background: Recommended management of Staphylococcus aureus bacteremia (SAB) includes follow-up blood culture sets (BCs) to determine the duration of bacteremia. Duration of bacteremia is an important prognostic factor in SAB, and follow-up BCs have a critical role in differentiation of uncomplicated and complicated SAB. However, intermittent negative BCs occur in SAB. Clinical guidelines for SAB management do not specify an approach to follow-up BCs' collection or define the number of negative BCs required to demonstrate resolution of bacteremia. This study assessed the frequency of intermittent negative BCs in SAB and used these findings to formulate a recommendation for collection of follow-up BCs. Methods: This retrospective study reviewed 1071 episodes of SAB. Clinical and microbiological data including the duration of bacteremia and the occurrence of intermittent negative BCs (those preceded and followed by positive cultures) were considered. Results: Intermittent bacteremia occurred in 13% (140/1071) of episodes. A single negative BC on days 1–3 had a predictive value of 87%–93% for resolution of bacteremia, although this was improved if all BCs collected within the same day were considered. Conclusions: Intermittent negative BCs are common in SAB. Given this, we would not recommend accepting a single negative BC as demonstrating resolution of the bacteremia. This is particularly important if a patient is to be classified as having uncomplicated SAB. Abstract : This study identified intermittent negative blood cultures in 13% of Staphylococcus aureus bacteremia episodes. As such the authors recommend that a single negative blood culture should never be accepted as sufficient evidence that bacteremia has resolved.